Thrombosis at unusual sites in reproductive age group-a case series - Mohd Tohit, Eusni Rahayu; Khalid, Bahariah; Seman, Zainina; Md Noor, Sabariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Thrombosis is one of the causes of morbidity and mortality in women of reproductive age group. Thrombosis at unusual sites may pose diagnostic and management dilemma for health care personnel. Teamwork and good communication provide the best modalities for maximum benefits to patients. Here with, we presented case a series of thrombosis at unusual sites seen and managed in our clinic. A 35 year-old Malay lady presented with left hemiparesis while she was on oestrogen based combined contraception pills (C-OCP). Imaging studies showed extensive venous thrombosis with bilateral acute cortical infarct. Thrombophilia screening of antiphospholipid syndrome were negative. She was put on anticoagulant and stopped 2 years after the incident. A 40 year-old Malay lady presented with abdominal discomfort, lethargy and massive splenomegaly. Bone marrow and trephine examination revealed primary myelofibrosis with positive JAK2617F. Imaging study showed chronic portal vein thrombosis with portal vein hypertension, complicated by gastro-oesophageal varices. She was put on hydroxyurea and later started on ruxolitinib with banding done over her gastro-oesophageal varices. A 26 year-old Malay lady presented with serositis, mouth ulcer and anaemia symptoms. Laboratory studies were positive for systemic lupus erythematosus and negative for antiphospholipid study. Imaging study showed long segment thrombosis of right internal jugular vein with surrounding subcutaneous oedema. She is currently stable on anticoagulants and steroid. Teamwork and holistic approach is practiced in the investigation and management to provide maximum benefits for patients.